Elastic response spectrum a historical note. - Chopra, Anil K. (Earthquake engineering & structural dynamics.)
This is the first contribution in a new series of Historical Notes on seminal concepts in earthquake engineering and structural dynamics. It records the origins and early developments (up to the late 1960's) of the elastic response spectrum.